Robust nonlinear PID-like fuzzy logic control of a planar parallel (2PRP-PPR) manipulator. (July 2016) - Londhe, P.S.; Singh, Yogesh; Santhakumar, M.; Patre, B.M.; Waghmare, L.M.
Abstract: In this paper, a robust nonlinear proportional–integral–derivative (PID)-like fuzzy control scheme is presented and applied to complex trajectory tracking control of a 2PRP-PPR (P-prismatic, R-revolute) planar parallel manipulator (motion platform) with three degrees-of-freedom (DOF) in the presence of parameter uncertainties and external disturbances. The proposed control law consists of mainly two parts: first part uses a feed forward term to enhance the control activity and estimated perturbed term to compensate for the unknown effects namely external disturbances and unmodeled dynamics, and the second part uses a PID-like fuzzy logic control as a feedback portion to enhance the overall closed-loop stability of the system. Experimental results are presented to show the effectiveness of the proposed control scheme. Abstract : Highlights: A comprehensive analysis of a planar parallel robot (2-PRP and 1-PPR) is presented. A robust nonlinear PID-like fuzzy tracking controller with disturbance compensation has been proposed. Applicability of the proposed controller has been demonstrated with prototype experiments. The robustness of the proposed controller is evaluated over existing controllers.